Non-invasive Quantification of Fat Deposits in Skeletal Muscle Predicts Cardiovascular Outcome in Kidney Failure - Keddar, Mehdi; Muylle, Thibaut; Carrie, Emmanuelle; Trefois, Pierre; Nachit, Maxime; Crott, Ralph; Christiaens, Claudine; Bammens, Bert; Jadoul, Michel; Goffin, Eric; Morelle, Johann (Frontiers in Physiology, 2020)
Fat accumulation in skeletal muscle was recently established as a major risk factor for cardiovascular disease (CVD) in the general population, but its relevance for patients with kidney failure is unknown. Here we examined the potential association between muscle radiation attenuation (MRA), a non-invasive indicator of fat deposits in muscle, and cardiovascular events in patients with kidney failure treated with peritoneal dialysis (PD) and investigated dynamic changes and determinants of MRA in this population. We retrospectively assessed MRA on computed tomography images collected yearly in 101 incident patients with kidney failure starting PD between January 2006 and December 2015. After a median of 21 months on dialysis, 34 patients had 58 non-fatal cardiovascular events, and 22 patients had died. Baseline MRA was associated with cardiovascular events during time on dialysis, and patients with higher MRA (reflecting lower amounts of fat in muscle) showed a reduced incidence of CVD, independently of traditional risk factors (adjusted HR, 0.91; 95% CI, 0.86–0.97, P = 0.006). Multivariate regression analysis identified old age, female gender, visceral fat area, and low residual urine volume as independent determinants of MRA. As compared with reference values from a healthy population, patients with kidney failure had lower MRA (i.e., increased fat accumulation), independently of age, gender, and body-mass index. The subset of patients who underwent kidney transplantation showed a significant increase in MRA after restoration of kidney function. These observations expand the association between ectopic fat accumulation and CVD to the population on dialysis, and suggest that kidney failure is reversibly associated with fatty muscle infiltration.